2011
DOI: 10.1155/2011/941876
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the Mechanisms of Resistance to Chemotherapy and Radiotherapy with the Cancer Stem Cell Hypothesis

Abstract: Despite advances in treatment, cancer remains the 2nd most common cause of death in the United States. Poor cure rates may result from the ability of cancer to recur and spread after initial therapies have seemingly eliminated detectable signs of disease. A growing body of evidence supports a role for cancer stem cells (CSCs) in tumor regrowth and spread after initial treatment. Thus, targeting CSCs in combination with traditional induction therapies may improve treatment outcomes and survival rates. Unfortuna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
149
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 204 publications
(153 citation statements)
references
References 117 publications
0
149
0
4
Order By: Relevance
“…Most recent studies have highlighted the heterogeneity of ovarian tumors, and the current understanding is that inherently chemoresistant cancer stem cells that are not removed by surgery and survive first-line chemotherapy are able to recreate the tumor and cause disease recurrence (4)(5)(6)(7)(8). Our group and others have demonstrated that within the heterogeneous tumor, CD44…”
Section: Introductionmentioning
confidence: 90%
“…Most recent studies have highlighted the heterogeneity of ovarian tumors, and the current understanding is that inherently chemoresistant cancer stem cells that are not removed by surgery and survive first-line chemotherapy are able to recreate the tumor and cause disease recurrence (4)(5)(6)(7)(8). Our group and others have demonstrated that within the heterogeneous tumor, CD44…”
Section: Introductionmentioning
confidence: 90%
“…It is well known that most solid tumors contain a distinct subpopulation of cancer stem cells (CSCs), which represent the source for tissue renewal, hold malignant potential and can be responsible for therapy resistance [3][4][5][6], and it has been suggested that a successful cure of cancer should requires eradication of CSCs [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Several of these characteristics are believed to be important in the resistance of CSC to traditional chemotherapy and radiation. 63,73,[79][80][81][82][83][84] The ability of CSC to leverage these characteristics to better handle environmental stresses and genotoxic damage potentially explains the disconnect between therapeutic response (ie, tumor burden reduction) and overall survival in the clinic. Tumors can all but be eradicated; however, if CSC persist, tumors will inevitably recur and are likely to be more aggressive given the genotoxic insults survived.…”
Section: Pdx Models and The Resurrection Of Tumor Stem Cellsmentioning
confidence: 99%